Clinical characteristics and potential aetiologies of non‐B non‐C hepatocellular carcinoma in hepatitis B virus endemic area. (24th March 2016) - Lee, Seung Bum; Kim, Kang Mo; An, Jihyun; Lee, Danbi; Shim, Ju Hyun; Lim, Young‐Suk; Lee, Han Chu; Chung, Young‐Hwa; Lee, Yung Sang
Abstract: Background & Aims: We investigated potential aetiologies, clinical characteristics and prognosis of non‐B non‐C (NBNC) hepatocellular carcinoma (HCC) patients in hepatitis B virus (HBV) endemic area, according to potential causes such as previous HBV exposure, chronic alcohol intake and metabolic syndrome. Patients and Methods: Among 4690 HCC patients treated at Asan Medical Center between 2007 and 2009, 523 were newly diagnosed with NBNC HCC, and their medical records and survival data were analyzed retrospectively. Results: Among 321 NBNC HCC patients whose hepatitis B core antibody (anti‐HBc) test results were available, 81.0%, 37.1% and 15.5% had anti‐HBc positivity, chronic alcohol intake and metabolic syndrome respectively. One‐hundred and fifty‐two patients (47.4%) had previous exposure to HBV without chronic alcohol intake or metabolic syndrome. Hepatitis B surface antibody (anti‐HBs) was positive in 48.0% of the 523 NBNC HCC patients, which was much lower than that in general Korean population, and 52.3% of anti‐HBc‐positive NBNC HCC patients were negative for anti‐HBs. Anti‐HBc‐negative alcoholic patients presented with more advanced cirrhosis with Child‐Pugh class B/C liver function than anti‐HBc‐positive patients ( P = 0.002). In multivariate analysis, baseline liver function, alpha‐foetoprotein levels and tumour stage were significant prognostic factors and aetiology did not affect patient survival. Conclusions: Prior HBV infection could be a potential aetiology in over 40% of NBNC HCC patients in HBV endemic area. Positivity for anti‐HBc and negativity for anti‐HBs may be a serologic surrogate marker for occult HBV infection in these area. The prognosis of NBNC HCC was determined by tumour stage and underlying liver function.